Métodos de escarificación en la germinación de semillas de kudzú pueraria phaseoloides - Alfaro Carvajal, Patricio Fernando (2015)
This research studies on the chemical and physical scarification by using hot water to accelerate the germination of tropical kudzu, important species plant cover in organic bananas, palm, performed at the Laboratory of fruit farming Faculty of Agricultural sciences with the following objectives: 1. Reduce the latency period by scarification methods Pueraria seed phaseoloides. 2. Determine the treatment and dose greater effect on germination and seedling growth.The materials used were Seeds kudzu, distilled water, sulfuric acid, lactic acid, acetic acid, beaker, petri dish, pipettes, thermometer, rule, covers nursery, agricultural soil, sand, rice chaff, agricultural lime, formalin, thermometer, camera, pallet identification. The treatments on seed scarification phaseoloides are Pueraria, sulfuric acid, lactic acid, acetic acid solutions the 2 and 5% and exposures seed 5 and 10 minutes and hot water at 70 °C, 80 °C and immersion times of 5 to 10 minutes, with 16 treatments and a control, soaking in water at room temperature. The treatments were arranged in a completely randomized experimental design; with 16 treatments, one witness and five replicates, with 68 experimental units or plastic bags with substrates of soil enriched with organic matter for planting five scarified with the above products seeds. Statistical analysis showed high statistical significance for the treatments in the six variables analyzed. The chemical scarification by using sulfuric acid courage successful in breaking the seed coat of tropical Kudzu facilitating the penetration of water to the embryo seed. Lactic and acetic acids caused a poor effect on woody seed coat so that the germination was low compared with that generated by sulfuric acid at 2% with immersion times of 5-10 minutes., The percentage of germination the seed did not exceed 56%, apparently low germination is typical of this forage species. The use of hot water at 70°C for times of 5 to 10 minutes was as efficient as the use of sulfuric acid, having statistically similar results to those obtained with acid mentioned above. And Height growth until 90 days was low but higher in plants from seeds scarified with hot water at 70 °C.This research studies on the chemical and physical scarification by using hot water to accelerate the germination of tropical kudzu, important species plant cover in organic bananas, palm, performed at the Laboratory of fruit farming Faculty of Agricultural sciences with the following objectives:1. Reduce the latency period by scarification methods Pueraria seed phaseoloides.2. Determine the treatment and dose greater effect on germination and seedling growth.The materials used were Seeds kudzu, distilled water, sulfuric acid, lactic acid, acetic acid, beaker, petri dish, pipettes, thermometer, rule, covers nursery, agricultural soil, sand, rice chaff, agricultural lime, formalin, thermometer, camera, pallet identification. The treatments on seed scarification phaseoloides are Pueraria, sulfuric acid, lactic acid, acetic acid solutions the 2 and 5% and exposures seed 5 and 10 minutes and hot water at 70 °C, 80 °C and immersion times of 5 to 10 minutes, with 16 treatments and a control, soaking in water at room temperature. The treatments were arranged in a completely randomized experimental design; with 16 treatments, one witness and five replicates, with 68 experimental units or plastic bags with substrates of soil enriched with organic matter for planting five scarified with the above products seeds. Statistical analysis showed high statistical significance for the treatments in the six variables analyzed. The chemical scarification by using sulfuric acid courage successful in breaking the seed coat of tropical Kudzu facilitating the penetration of water to the embryo seed. Lactic and acetic acids caused a poor effect on woody seed coat so that the germination was low compared with that generated by sulfuric acid at 2% with immersion times of 5-10 minutes., The percentage of germination the seed did not exceed 56%, apparently low germination is typical of this forage species. The use of hot water at 70°C for times of 5 to 10 minutes was as efficient as the use of sulfuric acid, having statistically similar results to those obtained with acid mentioned above. And Height growth until 90 days was low but higher in plants from seeds scarified with hot water at 70 °C.